PENGARUH KAPABILITAS PEMASARAN DAN KAPABILITAS INOVASI TERHADAP KEUNGGULAN BERSAING PADA UMKM KABUPATEN SUMBAWA - Kadewi Sumbawati, Novi; Syafruddin, Syafruddin; Kurniawansyah, Kurniawansyah; Karmeli, Elly (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of marketing capabilities and innovation capabilities on the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa District. Competitive advantage is a key factor in ensuring business sustainability amid increasingly intense market competition, changing consumer preferences, and rapid digital technological development. Marketing capability reflects the ability of MSMEs to understand customer needs, manage promotional strategies, build long-term relationships with customers, and effectively utilize digital media. Meanwhile, innovation capability refers to the ability of business actors to generate new ideas, develop products, improve production processes, and implement adaptive business models. This study adopts a quantitative approach with a causal research design to examine the cause-and-effect relationships among the variables studied. The research population consists of all MSMEs operating in Sumbawa District. Data were collected through the distribution of structured questionnaires to MSME owners/managers and analyzed using multiple linear regression. The results show that marketing capability and innovation capability have a positive and significant effect on the competitive advantage of MSMEs. This implies that the higher the ability of MSMEs to market their products and innovate, the greater their opportunities to survive and excel in an increasingly competitive business environment. These findings provide important implications for MSME actors and stakeholders in formulating strategies to strengthen competitiveness based on the enhancement of internal business capabilities.